Physical medicine & rehabilitation review questions - Ganesh, Shanti; Zelnik, Danielle (Philadelphia : Wolters Kluwer, 2019)
'This concise question-and-answer review for American Board of Physical Medicine & Rehabilitation (ABPMR) board review examinations boasts over 600 multiple-choice questions covering the general competencies, core knowledge, and the common topics critical for exam success and professional competency. You'll also find advice on how to approach the exam as well as test-taking tips and tactics. Written for anyone preparing for board review exams that certify ability to practice in the field of physical medicine and rehabilitation. Features numerous electrodiagnostic medicine questions. Includes a comprehensive chapter covering biostatistics, research, health policy, and epidemiology questions ideal for MD/MPH students. Links to a timed, computer-based practice test program to further help you hone your test-taking skills.'Pearls' at the end of each chapter offer key concepts and points to keep in mind when tackling relevant test section. Enrich Your eBook Reading Experience with Enhanced Video, Audio and Interactive Capabilities! Read directly on your preferred device(s), such as computer, tablet, or smartphone. Customize for your language, including right-to-left reading, vertical writing, and enhanced annotation in over 30 languages. Easily convert to audiobook, powering your content with natural language text-to-speech. Adapt for unique reading needs, supporting learning disabilities, visual/auditory impairments, second-language or literacy challenges, and more.'--Provided by publisher.
The low-down on the physical medicine and rehabilitation boards -- Musculoskeletal medicine -- Electrodiagnostic medicine -- Spine trauma and spinal cord injury medicine -- Stroke rehabilitation -- Amputee rehabilitation, prosthetics, and orthotics -- General rehabilitation -- Pediatric rehabilitation -- Traumatic brain injury -- Neuromuscular disorders and other neurologic conditions -- Fundamentals of rehabilitation therapy -- Health policy, research, and biostatistics.
This book includes online access at https://wolterskluwer.vitalsource.com/, please refer library staff for the password.
Includes bibliographical references and index.
Keywords: Physical and Rehabilitation Medicine; Rehabilitation